Genetic variants in telomere-maintaining genes and skin cancer risk - Nan, Hongmei (2010)
Telomere-related genes play an important role in maintaining the integrity of the telomeric structure that protects chromosome ends, and telomere dysfunction may lead to tumorigenesis. We evaluated the associations between 39 SNPs, including 38 tag-SNPs in telomere-related genes (TERT, TRF1, TRF2, TNKS2, and POT1) and one SNP (rs401681) in the TERT-CLPTM1L locus which has been identified as a susceptibility locus to skin cancer in the previous GWAS, and the risk of skin cancer in a case-control study of Caucasians nested within the Nurses’ Health Study (NHS) among 218 melanoma cases, 285 squamous cell carcinoma (SCC) cases, 300 basal cell carcinoma (BCC) cases, and 870 controls. Of the 39 SNPs evaluated, ten showed a nominal significant association with the risk of at least one type of skin cancer. After correction for multiple testing within each gene, two SNPs in the TERT gene (rs2853676 and rs2242652) and one SNP in the TRF1 gene (rs2981096) showed significant associations with the risk of melanoma. Also, the SNP rs401681 in the TERT-CLPTM1L locus was replicated for the association with melanoma risk. The additive odds ratio (OR) (95% confidence interval (95% CI)) of these four SNPs (rs2853676[T], rs2242652[A], rs2981096[G], and rs401681[C]) for the risk of melanoma was 1.43 (1.14–1.81), 1.50 (1.14–1.98), 1.87 (1.19–2.91), and 0.73 (0.59–0.91), respectively. Moreover, we found that the rs401681[C] was associated with shorter relative telomere length (p for trend, 0.05). We did not observe significant associations for SCC or BCC risk. Our study provides evidence for the contribution of genetic variants in the telomere-maintaining genes to melanoma susceptibility.